Understanding The Pythagorean Theorem Through The Area of a Square - Khathibul Umam Zaid Nugroho; YL Sukestiyarno; Sugiman Sugiman; M. Asikin (International Conference on Science, Education, and Technology, 2022)
Abstrak. Pyhtagoras' Theorem is a very important principle in mathematics, but many elementary students find it difficult to understand it. Therefore, this study aims to describe the quality of student responses in finding the Pythagorean formula. It is a descriptive-qualitative study to obtain a collection of students' thought processes and actions. The research subjects were selected based on their abstraction characteristics which could be classified into five groups. They are pre-structural, unistructural, multistructural, relational and extended-abstract. Students who become research subjects are elementary school students in Bengkulu City, Indonesia. The subjects of this study were twenty five people. The research instrument is the researcher himself who is guided by student assignments. Task-based interviews were applied to collect complete data. It is data collection using audio-visual recording. This data collection technique ensures that the data collected is complete and accurate. It is the genetic decomposition of the research subject. The results of this study are 3 students with pre-structural character, 5 unistructural students, 9 multistructural students, 7 relational students and 1 extended-abstract student. The conclusion of the study is that there are relational students who are able to coherently combine separate pieces of information and find the Pythagorean formula.